2016
DOI: 10.18632/oncotarget.12386
|View full text |Cite
|
Sign up to set email alerts
|

KRASmutations in blood circulating cell-free DNA: a pancreatic cancer case-control

Abstract: The utility of KRAS mutations in plasma circulating cell-free DNA (cfDNA) samples as non-invasive biomarkers for the detection of pancreatic cancer has never been evaluated in a large case-control series. We applied a KRAS amplicon-based deep sequencing strategy combined with analytical pipeline specifically designed for the detection of low-abundance mutations to screen plasma samples of 437 pancreatic cancer cases, 141 chronic pancreatitis subjects, and 394 healthy controls. We detected mutations in 21.1% (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 53 publications
3
62
1
Order By: Relevance
“…We compared the performance of our approach in measuring KRAS mutations with that in previous reports using PCR- or NGS-based methods ( Table S4 ). (Allenson et al, 2017; Berger et al, 2016; Brychta et al, 2016; Cheng et al, 2017; Cohen et al, 2017; Hadano et al, 2016; Kim et al, 2018; Kinugasa et al, 2015; Le Calvez-Kelm et al, 2016; Pietrasz et al, 2017; Sausen et al, 2015; Sefrioui et al, 2017; Takai et al, 2015) Across 13 high-quality studies, the detection rate of the KRAS mutations in plasma ranged from to 21% to 76% ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…We compared the performance of our approach in measuring KRAS mutations with that in previous reports using PCR- or NGS-based methods ( Table S4 ). (Allenson et al, 2017; Berger et al, 2016; Brychta et al, 2016; Cheng et al, 2017; Cohen et al, 2017; Hadano et al, 2016; Kim et al, 2018; Kinugasa et al, 2015; Le Calvez-Kelm et al, 2016; Pietrasz et al, 2017; Sausen et al, 2015; Sefrioui et al, 2017; Takai et al, 2015) Across 13 high-quality studies, the detection rate of the KRAS mutations in plasma ranged from to 21% to 76% ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…As obvious limitations exist while detecting gene mutations in tumor tissues, cfDNA has attracted more and more attention due to its more feasible, timely, and less invasive nature . For example, in pancreatic cancer, KRAS mutations in cfDNA were evaluated using deep sequencing assay as non‐invasive biomarkers in a large case‐control study and its changes between preoperation and postoperation were suggested to be a predictive biomarker for survival and treatment response . Currently, the KRAS status of primary tumors in CRC patients is considered as a reliable selection criterion prior to the application of EGFR‐targeted therapy .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, analysing the role of ctDNA in the early detection of small-cell lung cancer, the TP53 mutations were present in the plasma of 11% of the 225 non-cancer controls (Fernandez-Cuesta et al, 2016). Lastly, the KRAS cell-free DNA mutations could be detected in 3.7% of healthy controls and in 4.3% of patients with chronic pancreatitis in a study focused on pancreatic cancer detection (Calvez-Kelm et al, 2016).…”
Section: Circulating Tumour Dnamentioning
confidence: 99%